Impact of high penetration of electric vehicles on distribution network design - Ang, Chin Kiat (Nanyang Technological University, 2022)
Vehicles with Internal Combustion Engine (ICE) produces CO2 emission due to combustion has given rise to air pollution and global warming. The advent of global warming and the well-known fact that cars are the largest source of environmental pollutants, it has brought about car manufacturers to readdress the vehicles blueprint. Hence, the introduction of Electric vehicles can sufficiently reduce carbon emission. Electric vehicles (EVs) have been advancing significantly with its battery capacity. It provides more milage and decrease in charging time required with fast charging technology, making it more attractive to buyers. In addition, they are low emission and give positive effect on climate. Hence, the demand of EVs is likely to increases in the future. This can result to high charging load on existing distribution network. This report will investigate effect on electric vehicles (EVs) on distribution network design. It will provide extensive review on optimization of charging approaches used for EVs charging. In addition, different function of existing distribution network being supported by various renewable energy source, minimizing of peak load and different level of charging.